STUDY OF CRYSTAL STRUCTURE OF ZnO 0.6 M NANOPARTICLES SYNTHESIZED USING MORINGA LEAF (MORINGA OLEIFERA) EXTRACT AT PH-9 AND PH-10: STUDI STRUKTUR KRISTAL NANOPARTIKEL ZNO 0.6 M YANG DISINTESIS MENGGUNAKAN EKSTRAK DAUN KELOR (MORINGA OLIEFERA) PADA PH-9 DAN PH-10 - Annisa Feby Nur Rahmasari; Iwan Sugihartono; Nurfina Yudasari; Akhmad Futukhillah Fataba Alaih; Djoko Triyono (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
ZnO 0.6 M nanoparticles have been successfully synthesized using the precipitation method by mixing 5.68 grams of zinc nitrate tetrahydrate precursor with 50 ml of moringa leaf liquid extract for 30 minutes at 80ºC during the stirring process with variations in pH 9 and pH 10. The synthesized precipitate was calcined at 450ºC for 2 hours. Tests using X-ray Diffraction (XRD) techniques were carried out to analyze diffraction patterns and crystal structure parameters. Based on Inorganic Crystal Structure Database (ICSD) numbers #96-900-4181 and #96-900-4182, ZnO nanoparticles have a hexagonal crystal structure with space group P63mc. ZnO 0.6 M pH 9 has an average crystallite size of 57.83 nm and ZnO 0.6 M pH 10 has an average crystallite size of 48.57 nm. The crystallite size at pH 9 and pH 10 shows a change in size in the nanomaterial and has a difference of 9.22 nm. Crystal structure parameters are lattice parameters a = b = 3.24 Å and c = 5.20 Å and unit cell volume = 47.63 Å.